A new species of Tripogon (Poaceae: Chloridoideae: Tripogoninae) from Nallamala forests, Telangana, India - Rasingam, Ladan; Swamy, Jetti (Phytotaxa, 2018)
A new species Tripogon nallamalayanus is described from Nagarjunasagar Srisailam Tiger Reserve of Nallamala forests, Telangana, India. This new species most closely resembles Tripogon trifidus, but differs in spikelets and lower glumes lengths and lemma and palea shapes.